Rural Community Tourism Networks: The experience of Argentina and Costa Rica - Murillo-Soto, Valeria (2016)
In this article some results of a research that was conducted in the late 2014 are presented. The objective of research was to describe the relationship between networks that support Rural Community Tourism (TRC) and their entrepreneurs.  Two supporting organizations were chosen: Alianza Conservacionista de Turismo Alternativo de Costa Rica (ACTUAR) and Red Argentina de Turismo Rural Community (RATURC).Links among networks and entrepreneurs were determined by a survey taken to entrepreneurs who belong to CBOs. The application of the survey allowed to obtain demographic variables, and general data of rural tourism businesses, marketing, and communication between networks and affiliates. The results indicated, in relation to both organizations, that entrepreneurs perceive them as providers of tools to improve performance. In the case of Argentina, support from the State and linkage with it are more manifest than in Costa Rica. Results also evidenced that there is staff trained to provide assistance to tourists, in both cases.